2010
DOI: 10.1098/rsif.2010.0194
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of tumour morphological stability and evaluation against experimental observations

Abstract: The hallmark of malignant tumours is their spread into neighbouring tissue and metastasis to distant organs, which can lead to life threatening consequences. One of the defining characteristics of aggressive tumours is an unstable morphology, including the formation of invasive fingers and protrusions observed both in vitro and in vivo. In spite of extensive biological, clinical and modelling study and research at physical scales ranging from the molecular to the tissue, the driving dynamics of tumour invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…The authors showed the existence of a logarithmically slow coarsening regime that arises when the phase domains are comparable to the average pore size. The system (1.2) -(1.4) is also closely related to models of tumor growth [20,33,34] which include an additional mass source for volumetric growth. When the surface tension vanishes, i.e., γ = 0, the CHB system reduces to the CahnHilliard equation [3].…”
Section: Problem Definition and Backgroundmentioning
confidence: 99%
“…The authors showed the existence of a logarithmically slow coarsening regime that arises when the phase domains are comparable to the average pore size. The system (1.2) -(1.4) is also closely related to models of tumor growth [20,33,34] which include an additional mass source for volumetric growth. When the surface tension vanishes, i.e., γ = 0, the CHB system reduces to the CahnHilliard equation [3].…”
Section: Problem Definition and Backgroundmentioning
confidence: 99%
“…Enhancing the positive feedback on SC self-renewal increases both tumor and SC volume and prompts new SC clusters and the splitting of existing clusters, resulting in increased shape complexity that indicates a more invasive tumor. We note that the link between unstable morphologies and tumor invasion has been suggested in Bearer et al (2009) and Pham et al (2011). In contrast, negative feedback inhibits tumor growth and SC pattern formation by enhancing SC differentiation, which results in a more compact and less invasive tumor.…”
Section: Discussionmentioning
confidence: 57%
“…11 shows the evolution of the stability of the circular tumor as a function of the control parameter T , also found in a one phase model [109] . The physical origin of this "buckling" criteria is simply the fact that localized Fig.…”
Section: Numerical Resultsmentioning
confidence: 89%